Estudo computacional da viscosidade da água confinada em nanotubos de carbono - Köhler, Mateus Henrique (2015)
When confined in nanometer scale, water presents great variation in their dynamic properties. Here, we carried out molecular dynamics simulations to determine the ratio of the diffusion coefficient and viscosity variation of water confined in carbon nanotubes with different diameters. We have found that both properties are affected by confinement. While the difusion has not monotonic growth with the diameter, the viscosity varies with its fifth root. Furthermore, the viscosity of the contained water is an order of magnitude lower than that of bulk water. By varying the density of water within the pore, we observed that the viscosity is deeply affected, reaching values 300% higher when density is increased by 40%. In addition, we tested the impact of the thermostat selection on viscosity s determination, concluding that the thermostat Langevin has higher values for both the contained water and to the bulk.